Renewable Energy and Its Applications Around the World - Hojjatie, Barry (My University, 2020)
Energy is the main and most inclusive measure of all the wide ranges of work done by humans and machines. Renewable energies such as solar, hydro, wind and so forth have become crucial since they neithert create any pollution nor require imported fuel. For achieving growth and progress in developing countries, the utilization of available energy sources is important. Renewable energy can be cost-efficient and socially more beneficial. This research provides us a look into how some countries in Africa, Europe, Asia, and Australia take advantage of renewable energy sources and explore its vast possibilities. Finding alternative energy sources that reduce costs and compete with fossil fuels; the study will look into the dynamics of the competitive transition and what these countries are innovating to make sustainable energy strong.